2023
DOI: 10.1038/s41467-023-36937-8
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime over 10000 hours for organic solar cells with Ir/IrOx electron-transporting layer

Abstract: The stability of organic solar cells is a key issue to promote practical applications. Herein, we demonstrate that the device performance of organic solar cells is enhanced by an Ir/IrOx electron-transporting layer, benefiting from its suitable work function and heterogeneous distribution of surface energy in nanoscale. Notably, the champion Ir/IrOx-based devices exhibit superior stabilities under shelf storing (T80 = 56696 h), thermal aging (T70 = 13920 h), and maximum power point tracking (T80 = 1058 h), com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 71 publications
1
28
0
1
Order By: Relevance
“…The smallest arc radius is found for P, N–C@CNHS (Figure b), which indicates the fastest transfer of photo-generated carriers. , Meanwhile, the Bode-phase plot was measured and is shown in Figure c. The electron lifetime (τ r ) tends to be relevant to the inverse of characteristic frequency peaks following eq . , Correspondingly, the more negative frequency peak indicates a faster electron transfer and lower carrier recombination rate of P, N–C@CNHS. Additionally, as shown in Figure d, all photocatalysts display good photo-response ability, and P, N–C@CNHS presents the highest photocurrent signal. τ normalr = 1 / ( 2 π f max ) where f max is set as the maximum frequency of a specific peak for the intermediate. E normalC normalB = E normalV normalB E normalg normalO 2 + normalH + + 2 normale normalH 2 normalO 2 …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The smallest arc radius is found for P, N–C@CNHS (Figure b), which indicates the fastest transfer of photo-generated carriers. , Meanwhile, the Bode-phase plot was measured and is shown in Figure c. The electron lifetime (τ r ) tends to be relevant to the inverse of characteristic frequency peaks following eq . , Correspondingly, the more negative frequency peak indicates a faster electron transfer and lower carrier recombination rate of P, N–C@CNHS. Additionally, as shown in Figure d, all photocatalysts display good photo-response ability, and P, N–C@CNHS presents the highest photocurrent signal. τ normalr = 1 / ( 2 π f max ) where f max is set as the maximum frequency of a specific peak for the intermediate. E normalC normalB = E normalV normalB E normalg normalO 2 + normalH + + 2 normale normalH 2 normalO 2 …”
Section: Resultsmentioning
confidence: 97%
“…The electron lifetime (τ r ) tends to be relevant to the inverse of characteristic frequency peaks following eq 3. 62,63 Correspondingly, the more negative frequency peak indicates a faster electron transfer and lower carrier recombination rate of P, N−C@CNHS. Additionally, as shown in Figure 4d, all photocatalysts display good photoresponse ability, and P, N−C@CNHS presents the highest photocurrent signal.…”
Section: Mechanism For Enhanced Photocatalytic H 2 O 2 Production Cha...mentioning
confidence: 98%
“…According to reports, PEDOT:PSS can improve its performance by acid treatment, and the H + ions contained in H x MoO 3 may also play the same role. Device stability is a key issue to promote practical applications. , Figure shows the normalized functions of the thermal stability of PCE, V oc , J sc , and FFfour parameters of different HTL devices exposed to an 85°C nitrogen environment under unpackaged conditions within 400 h, where HTL is PEDOT:PSS, H x MoO 3 , and hybrid HTL. The detailed data are recorded in Tables S4–S6.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, studies have been reported to improve efficiency and stability by applying ethoxylated polyethyleneimine chelated with Zn 2þ or iridium/ iridium oxide without using ZnO, but it is difficult to avoid the application of ZnO in terms of cost or ease of use. [45,46] In this study, defects were effectively decreased from the ZnO surface by electron beam annealing (EBA). EBA treatment can improve the physical properties of thin films in a relatively low temperature and short time compared to conventional thermal treatment.…”
Section: Doi: 101002/solr202300178mentioning
confidence: 99%